The impact of a 12-week high-intensity interval training program on popliteal vascular responses to prolonged sitting - Haoxuan Liu; Sophie E. Rayner; Beverly D. Schwartz; Yanlin Wu; Jennifer L. Petterson; Myles W. O’Brien; Derek Stephen Kimmerly (European Journal of Applied Physiology, 2026)

The Importance of Scale in the Definition of Uncertainties: How do we Best Communicate this to Data Users? - Claire E. Bulgin; Paul Green; Alexander Gruber; Claire Macintosh; Jonathan Mittaz; Ashley Ramsay; Nick A. Rayner (Surveys in Geophysics, 2025)
Climate services often require observational climate data to inform decision-making on mitigation and adaptation activities. Understanding the uncertainties in the climate datasets that are used for this purpose, and how these uncertainties relate to the context of the climate service is critical to making well-informed decisions. Recent developments in the production of climate-relevant satellite datasets has focused on characterising uncertainties from a bottom-up perspective with a high degree of mathematical rigour. Using the example of three essential climate variables: sea surface temperature, soil moisture and carbon dioxide we discuss how to translate the highly-detailed uncertainty information provided with high-resolution datasets into something appropriate to the scale of a climate service, where the decision-making context might be local, regional or global. Close engagement between climate data producers and climate service providers is essential to ensure we have the best possible platform to make decisions as we adapt to climate change.

Refining seasonal performance metrics for room air-conditioning in emerging markets: Integrating building simulations with real-world equipment performance data - Mateus Bavaresco; Rayner Maurício e Silva Machado; Amanda F. Krelling; Ana Paula Melo; Won Young Park; Roberto Lamberts (Energy and Buildings, 2025)

Clear-white plastics are most common in global oceans and seabird stomachs, but local species can ingest specific colours - Ariel-Micaiah Heswall; Matt Rayner; Brian N. Wijaya; Lynn Miller; Kristal E. Cain; Megan R. Friesen; Anne C. Gaskett (Marine Pollution Bulletin, 2025)

Quantifying taxon-specific habitat connectivity requirements of urban wildlife using structured expert judgement - Stephanie K. Courtney Jones; Luke S. O'Loughlin; Danswell Starrs; Jacinta E. Humphrey; Stephanie A. Pulsford; Hugh Allan; Matt Beitzel; Kym Birgen; Suzi Bond; Jenny Bounds; Deborah Bower; Renee Brawata; et al. (Biological Conservation, 2025)

Around the World in 26 Million Years: Diversification and Biogeography of Pantropical Grass‐Yellow Eurema Butterflies (Pieridae: Coliadinae) - Jing V. Leong; Pável Matos‐Maraví; Rayner Núñez; Renato Nunes; Weijun Liang; Michael F. Braby; Tenzing Doleck; Kwaku Aduse‐Poku; Yutaka Inayoshi; Yu‐Feng Hsu; Niklas Wahlberg; Djunijanti Peggie; et al. (Journal of Biogeography, 2025)
Aim Grass‐yellow butterflies ( Eurema ) are a group of pantropical Pieridae distributed throughout Asia, Australasia, Africa and the New World. However, little is known about their diversification, including the biogeographic mechanism(s) explaining their circumglobal distribution. We present the first densely sampled, time‐calibrated phylogeny and biogeographic reconstruction of grass‐yellows to confirm the monophyly of the genera, re‐evaluate their taxonomy and infer the biogeographic events contributing to their worldwide distribution. Location Global tropics and subtropics. Taxon The butterfly tribe Euremini (Pieridae: Coliadinae). Methods We analysed up to 391 genetic loci from 126 samples of 66 ingroup species. Divergence dating was accomplished in a Bayesian phylogenetic framework using secondary calibration points, and maximum likelihood models of various biogeographic models were fitted to the data using the R package BioGeoBEARS. We used the best fitting model to estimate relative dispersal events with biogeographical stochastic mapping. Finally, we estimated branch‐specific speciation and extinction rates to assess the diversification history of the group. Results Different phylogenomic analyses converged on similar topologies with robust support. Grass‐yellows emerged ca . 26 Mya in the New World, and a single extant lineage dispersed to Asia in the early Miocene, where they diversified and dispersed to Africa and Australasia. The fastest rates of diversification occurred in the Old World tropics during the late Miocene. Many of the grass‐yellow genera were either paraphyletic or polyphyletic as traditionally circumscribed. To maintain nomenclatural stability, we place all grass‐yellows in Eurema sensu lato and recognise two subgenera: Eurema ( Abaeis ) and Eurema ( Eurema ). Main Conclusions Grass‐yellow butterflies originated in the Americas and attained their global distributional patterns via dispersal. The Indo‐Australian and Caribbean archipelagoes seem to have accelerated the diversification of the group, and movement in and out of these island regions was frequent. Although the traditional view of founder‐event speciation envisions migrants from large landmasses (‘mainland’) colonising smaller landmasses (‘islands’), we find that island to mainland dispersal and differentiation were equally or more common.

The impact of climate data uncertainty on bioclimatic zoning for building design - Rayner Maurício e Silva Machado; Facundo Bre; Ana Paula Melo; Roberto Lamberts (Building and Environment, 2025)

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Bioclimatic zoning for building performance using tailored clustering method and high-resolution climate data - Rayner Maurício e Silva Machado; Facundo Bre; Leonardo Mazzaferro; Ana Paula Melo; Roberto Lamberts (Energy and Buildings, 2024)

Metamodel to predict annual cooling thermal load for commercial, services and public buildings: A country-level approach to support energy efficiency regulation - Rayner Maurício e Silva Machado; Matheus Soares Geraldi; Mateus Bavaresco; Marcelo Salles Olinger; Larissa Pereira de Souza; Artur Martins Kamimura; Natasha Hansen Gapski; Tiago de Castro Quevedo; Liége Garlet; Ana Paula Melo; Roberto Lamberts (Energy and Buildings, 2023)

Energy efficiency strategies for Brazilian social housing considering a life cycle perspective: Optimisation between thermal autonomy, energy consumption and costs - Maria Andrea Triana; Rayner Mauricio e Silva Machado; Artur Martins Kamimura; Matheus Körbes Bracht; Ana Paula Melo; Roberto Lamberts (Energy and Buildings, 2023)

Comparative pathology of VIC01 isolate and Omicron variant of SARS-CoV-2 infection, including a rechallenge model, in the Golden Syrian hamster - E. Rayner; K. Ryan; Y. Hall; L. Hunter; C. Kennard; J. Edun Hughes; J. Salguero Bodes (Journal of Comparative Pathology, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Transcriptomic Response of Primary Human Bronchial Cells to Repeated Exposures of Cigarette and ENDS Preparations - Rachael E. Rayner; Jack Wellmerling; Patrudu Makena; Jing Zhao; G. L. Prasad; Estelle Cormet-Boyaka (Cell Biochemistry and Biophysics, 2022)

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Pending recovery in the strength of the meridional overturning circulation at 26° N - Ben I. Moat; David A. Smeed; Eleanor Frajka-Williams; Damien G. Desbruyères; Claudie Beaulieu; William E. Johns; Darren Rayner; Alejandra Sanchez-Franks; Molly O. Baringer; Denis Volkov; Laura C. Jackson; Harry L. Bryden (Ocean Science, 2020)
The strength of the Atlantic meridional overturning circulation (AMOC) at 26∘ N has now been continuously measured by the RAPID array over the period April 2004–September 2018. This record provides unique insight into the variability of the large-scale ocean circulation, previously only measured by sporadic snapshots of basin-wide transport from hydrographic sections. The continuous measurements have unveiled striking variability on timescales of days to a decade, driven largely by wind forcing, contrasting with previous expectations about a slowly varying buoyancy-forced large-scale ocean circulation. However, these measurements were primarily observed during a warm state of the Atlantic multidecadal variability (AMV) which has been steadily declining since a peak in 2008–2010. In 2013–2015, a period of strong buoyancy forcing by the atmosphere drove intense water-mass transformation in the subpolar North Atlantic and provides a unique opportunity to investigate the response of the large-scale ocean circulation to buoyancy forcing. Modelling studies suggest that the AMOC in the subtropics responds to such events with an increase in overturning transport, after a lag of 3–9 years. At 45∘ N, observations suggest that the AMOC may already be increasing. Examining 26∘ N, we find that the AMOC is no longer weakening, though the recent transport is not above the long-term mean. Extending the record backwards in time at 26∘ N with ocean reanalysis from GloSea5, the transport fluctuations at 26∘ N are consistent with a 0- to 2-year lag from those at 45∘ N, albeit with lower magnitude. Given the short span of time and anticipated delays in the signal from the subpolar to subtropical gyres, it is not yet possible to determine whether the subtropical AMOC strength is recovering nor how the AMOC at 26∘ N responds to intense buoyancy forcing.

ICOADS Release 3.0: a major update to the historical marine climate record - Eric Freeman; Scott D. Woodruff; Steven J. Worley; Sandra J. Lubker; Elizabeth C. Kent; William E. Angel; David I. Berry; Philip Brohan; Ryan Eastman; Lydia Gates; Wolfgang Gloeden; Zaihua Ji; et al. (International Journal of Climatology, 2017)
We highlight improvements to the International Comprehensive Ocean‐Atmosphere Data Set ( ICOADS ) in the latest Release 3.0 ( R3 .0; covering 1662–2014). ICOADS is the most widely used freely available collection of surface marine observations, providing data for the construction of gridded analyses of sea surface temperature, estimates of air–sea interaction and other meteorological variables. ICOADS observations are assimilated into all major atmospheric, oceanic and coupled reanalyses, further widening its impact. R3 .0 therefore includes changes designed to enable effective exchange of information describing data quality between ICOADS , reanalysis centres, data set developers, scientists and the public. These user‐driven innovations include the assignment of a unique identifier ( UID ) to each marine report – to enable tracing of observations, linking with reports and improved data sharing. Other revisions and extensions of the ICOADS ' International Maritime Meteorological Archive common data format incorporate new near‐surface oceanographic data elements and cloud parameters. Many new input data sources have been assembled, and updates and improvements to existing data sources, or removal of erroneous data, made. Coupled with enhanced ‘preliminary’ monthly data and product extensions past 2014, R3 .0 provides improved support of climate assessment and monitoring, reanalyses and near‐real‐time applications.

Body size drives allochthony in food webs of tropical rivers - Timothy D. Jardine; Thomas S. Rayner; Neil E. Pettit; Dominic Valdez; Douglas P. Ward; Garry Lindner; Michael M. Douglas; Stuart E. Bunn (Oecologia, 2017)

Compensation between meridional flow components of the Atlantic MOC at 26° N - E. Frajka-Williams; C. S. Meinen; W. E. Johns; D. A. Smeed; A. Duchez; A. J. Lawrence; D. A. Cuthbertson; G. D. McCarthy; H. L. Bryden; M. O. Baringer; B. I. Moat; D. Rayner (Ocean Science, 2016)
From ten years of observations of the Atlantic meridional overturning circulation (MOC) at 26° N (2004–2014), we revisit the question of flow compensation between components of the circulation. Contrasting with early results from the observations, transport variations of the Florida Current (FC) and upper mid-ocean (UMO) transports (top 1000 m east of the Bahamas) are now found to compensate on sub-annual timescales. The observed compensation between the FC and UMO transports is associated with horizontal circulation and means that this part of the correlated variability does not project onto the MOC. A deep baroclinic response to wind-forcing (Ekman transport) is also found in the lower North Atlantic Deep Water (LNADW; 3000–5000 m) transport. In contrast, co-variability between Ekman and the LNADW transports does contribute to overturning. On longer timescales, the southward UMO transport has continued to strengthen, resulting in a continued decline of the MOC. Most of this interannual variability of the MOC can be traced to changes in isopycnal displacements on the western boundary, within the top 1000 m and below 2000 m. Substantial trends are observed in isopycnal displacements in the deep ocean, underscoring the importance of deep boundary measurements to capture the variability of the Atlantic MOC.

Cities are hotspots for threatened species - Christopher D. Ives; Pia E. Lentini; Caragh G. Threlfall; Karen Ikin; Danielle F. Shanahan; Georgia E. Garrard; Sarah A. Bekessy; Richard A. Fuller; Laura Mumaw; Laura Rayner; Ross Rowe; Leonie E. Valentine; et al. (Global Ecology and Biogeography, 2016)
Aim Although urbanization impacts many species, there is little information on the patterns of occurrences of threatened species in urban relative to non‐urban areas. By assessing the extent of the distribution of threatened species across all A ustralian cities, we aim to investigate the currently under‐utilized opportunity that cities present for national biodiversity conservation. Location A ustralian mainland, T asmania and offshore islands. Methods Distributions of A ustralia's 1643 legally protected terrestrial species (hereafter ‘threatened species’) were compiled. We assessed the extent to which they overlapped with 99 cities (of more than 10,000 people), with all non‐urban areas, and with simulated ‘dummy’ cities which covered the same area and bioregion as the true cities but were non‐urban. We analysed differences between animals and plants, and examined variability within these groups using species accumulation modelling. Threatened species richness of true versus dummy cities was analysed using generalized linear mixed‐effects models. Results A ustralian cities support substantially more nationally threatened animal and plant species than all other non‐urban areas on a unit‐area basis. Thirty per cent of threatened species were found to occur in cities. Distribution patterns differed between plants and animals: individual threatened plant species were generally found in fewer cities than threatened animal species, yet plants were more likely to have a greater proportion of their distribution in urban areas than animals. Individual cities tended to contain unique suites of threatened species, especially threatened plants. The analysis of true versus dummy cities demonstrated that, even after accounting for factors such as net primary productivity and distance to the coast, cities still consistently supported a greater number of threatened species. Main conclusions This research highlights that A ustralian cities are important for the conservation of threatened species, and that the species assemblages of individual cities are relatively distinct. National conservation policy should recognize that cities play an integral role when planning for and managing threatened species.

Observed decline of the Atlantic meridional overturning circulation 2004–2012 - D. A. Smeed; G. D. McCarthy; S. A. Cunningham; E. Frajka-Williams; D. Rayner; W. E. Johns; C. S. Meinen; M. O. Baringer; B. I. Moat; A. Duchez; H. L. Bryden (Ocean Science, 2014)
The Atlantic meridional overturning circulation (AMOC) has been observed continuously at 26° N since April 2004. The AMOC and its component parts are monitored by combining a transatlantic array of moored instruments with submarine-cable-based measurements of the Gulf Stream and satellite derived Ekman transport. The time series has recently been extended to October 2012 and the results show a downward trend since 2004. From April 2008 to March 2012, the AMOC was an average of 2.7 Sv (1 Sv = 106 m3 s−1) weaker than in the first four years of observation (95% confidence that the reduction is 0.3 Sv or more). Ekman transport reduced by about 0.2 Sv and the Gulf Stream by 0.5 Sv but most of the change (2.0 Sv) is due to the mid-ocean geostrophic flow. The change of the mid-ocean geostrophic flow represents a strengthening of the southward flow above the thermocline. The increased southward flow of warm waters is balanced by a decrease in the southward flow of lower North Atlantic deep water below 3000 m. The transport of lower North Atlantic deep water slowed by 7% per year (95% confidence that the rate of slowing is greater than 2.5% per year).

Deformation, metamorphism, and mobilization of Ni–Cu–PGE sulfide ores at Garson Mine, Sudbury - Joshua Mukwakwami; Bruno Lafrance; C. Michael Lesher; Douglas K. Tinkham; Nicole M. Rayner; Doreen E. Ames (Mineralium Deposita, 2014)

Bioacoustic distances between the begging calls of brood parasites and their host species: a comparison of metrics and techniques - Louis Ranjard; Michael G. Anderson; Matt J. Rayner; Robert B. Payne; Ian McLean; James V. Briskie; Howard A. Ross; Dianne H. Brunton; Sarah M. N. Woolley; Mark E. Hauber (Behavioral Ecology and Sociobiology, 2010)

Central place foraging by breeding Cook’s petrel Pterodroma cookii: foraging duration reflects range, diet and chick meal mass - M. J. Rayner; B. W. Hartill; M. E. Hauber; R. A. Phillips (Marine Biology, 2010)

Mitochondrial DNA analysis reveals genetic structure in two New Zealand Cook’s petrel (Pterodroma cookii) populations - Matt J. Rayner; Colm J. F. Carraher; Mick N. Clout; Mark E. Hauber (Conservation Genetics, 2010)

Sodium butyrate induced keratinocyte apoptosis - Ilse S. Daehn; Antiopi Varelias; Timothy E. Rayner (Apoptosis, 2006)